تعليم اللغة العربيّة: مشكلات وحلول: Teaching Arabic Language: Problems and Solutions - Ahmed Hussein, Nasr El Din Ibrahim (Journal of Islamic Educational Research, 2020)
The research deals with some of the problems facing the Arabic language in the modern era, as the Arabic language faces multiple issues and challenges that have been raised around it, and this does not preclude saying its importance and its global position. The Arabic language is the language of the Noble Qur’an, and it was pronounced -in the past- by people of statement, and rhetoric, and they were dear to them, and they were proud of it. But in our time, it has suffered from various problems in its teaching and learning, and these problems have stood in the way of a dam in its teaching methods, and their proper absorption, and therefore we have been keen to expose these problems and try to find solutions to them. These problems lie in satellite channels, the internet, television, ’visual radio’, the press, the educational dimension, nannies, alienation, the phenomenon of naturalization, bilingualism, poor curricula, educational qualification, duality between vernacular and classical.